Dieta e Relação de Abundância de Panthera Onca e Puma Concolor Com suas Espécies-Presa na Amazônia Central - Prado, Denise Mello Do (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Jaguar, Panthera onca, and cougar, Puma concolor, occur sympatrically in most tropical and subtropical evergreen forests on the American continent and have often been classified as opportunistic predators. However, little is known about the feeding ecology of these felids in the Amazon region and about predator-prey abundance relationships. In this study, we analyzed the diet and prey availability of jaguar and cougar in 4 localities in northern central Amazonia. Diet was assessed through faecal analysis and prey availability was estimated by diurnal visual surveys and print traps. Predator relative abundance was estimated by print traps. The identity of the predators was determined by molecular analysis of feaces and the prey items were identified from hair structure. Overall dietary overlap was high, in terms of mass of different kind of prey killed. Small-prey (< 10 kg) was captured more by cougar than medium (10-30 kg) and large prey (>30 kg) in all localities. Jaguar consumed more small prey than other groups only in Ducke Reserve, but the large-sized prey (>30 kg) were the most frequent group in the other localities, which were analyzed together. Arboreal mammals, principally sloths, were found in high frequency in the diet of cougar and moderately in the diet of jaguar at Ducke Reserve. The relative-abundance indexes of jaguar and cougar tended to covary with the abundance indexes of medium-sized (10-30 kg) terrestrial mammals in all localities, but there was no tendency to covary with the abundance indexes of small (<10 kg) or large (>30 kg) mammals. The tendency to covary with mediumsized prey suggests they are the most important food sources for jaguar and cougar in the northern central Amazonian. Our results do not support a significant presence of mediumsized prey in jaguar and cougar diet. However, we had only a small sample of feces from Viruá, Uatumã and Maracá. In Ducke reserve, the low abundance of medium-sized prey is likely to be because of poaching. A literature review of jaguar and cougar diets from rainforest regions indicated that, in areas where there are no the white-tailed deer, Odocoileus virginianus (a large prey specie), medium-sized prey are the most frequent prey in jaguar and cougar diets. In the areas where O. virginianus occurs, it is the main prey of jaguar and cougar, resulting in a predominance of large prey (>30 kg) in the diet. Possibly, jaguar and cougar primarily consume large mammals where they occur in abundance, are easy to catch and are not dangerous to predators, but in areas where this group is scarce or dangerous, the main group of prey is the medium-sized mammals. When easily taken large and medium-prey are less abundant, jaguar and cougar take more small prey, as occurred in Ducke reserve. Our results provide further evidence of opportunistic in feeding behavior by jaguars and cougars.